2023
DOI: 10.1002/awwa.2067
|View full text |Cite
|
Sign up to set email alerts
|

The Future Workforce of the Environmental Laboratory

Abstract: Key Takeaways The environmental laboratory workforce is aging out and needs creative solutions to recruit and retain skilled staff to perform physical, microbial, chemical, and radiological tests. There are immediate needs for chemists to work in radiochemistry and to conduct analyses for per‐ and polyfluoroalkyl substances and other contaminants of emerging concern. Promoting the water and wastewater industry and developing the industry workforce require education through public outreach, internships, fellows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…They concluded that what's needed is a highly diverse workforce in terms of educational backgrounds, skill sets, and desired working conditions. One key issue identified was the need to bring in a young, talented workforce with a passion for protecting public health and the environment (Adams et al 2023b).…”
mentioning
confidence: 99%
“…They concluded that what's needed is a highly diverse workforce in terms of educational backgrounds, skill sets, and desired working conditions. One key issue identified was the need to bring in a young, talented workforce with a passion for protecting public health and the environment (Adams et al 2023b).…”
mentioning
confidence: 99%